Observed evidence for guideline‐recommended genes in predicting prostate cancer risk from a large population‐based cohort. Issue 13 (12th July 2021) - Wei, Jun; Yang, Wancai; Shi, Zhuqing; Lu, Lucy; Wang, Qiang; Resurreccion, W. Kyle; Engelmann, Valentina; Zheng, S. Lilly; Hulick, Peter J.; Cooney, Kathleen A.; Isaacs, William B.; Helfand, Brian T.; et al.
Abstract: Background: Germline testing for prostate cancer (PCa) is now recommended by the National Comprehensive Cancer Network. While multi‐gene testing has been proposed, evidence for their association with PCa risk is not well established. Methods: We tested associations of pathogenic/likely pathogenic mutations in 10 guideline‐recommended genes ( ATM, BRCA1, BRCA2, CHEK2, PALB2, MLH1, MSH2, MSH6, PMS2, and HOXB13 ) with PCa risk in the UK Biobank, a population‐based cohort. Mutations were annotated based on prostate‐specific transcripts using the American College of Medical Genetics and Genomics standards. Associations were tested in 4399 PCa cases and 85, 403 unaffected male controls using logistic regression adjusting for age and genetic background. p < .005 was considered significant based on Bonferroni correction. Results: Among the 10 tested genes, significantly higher mutation carrier rates in PCa cases versus controls were found for four genes at p < .005; HOXB13, BRCA2, ATM, and CHEK2, with odds ratios (95% confidence interval) estimated at 4.96 (3.62–6.69), 3.23 (2.23–4.56), 2.95 (2.01–4.22), 1.94 (1.43–2.58), respectively. No significant association was found between mutation carrier status and age at PCa diagnosis or family history of PCa. Despite the large sample size of this study, statistical power remains limited, especially for genes where pathogenic mutation carrier rates are extremely rare (<0.03%). Conclusion: Observed evidence for PCa risk was found for four of the 10 guideline‐recommended genes in this large population‐based study. Mutations in these four genes can be interpreted with confidence in genetic counseling for PCa risk assessment. Evidence for the remaining six genes needs to be further evaluated in larger studies.